Review of recent advances in Stirling-type pulse tube cryocoolers. (April 2019) - Dang, Haizheng; Tan, Jun; Zha, Rui; Li, Jiaqi; Zhang, Tao; Zhao, Yongjiang; Zhao, Bangjian; Tan, Han; Xue, Renjun
Abstract: This paper reviews recent advances in Stirling-type pulse tube cryocoolers (SPTCs) developed in the authors' laboratory, in which single- and two-stage coolers cover 10–150 K while three- and four-stage ones operate at 4–10 K. The cooling capacities vary from 1.0 W for optical and electronic devices to 580 W at 77 K for superconducting cables, while the overall masses range from 700 g to 180 kg. The three-stage SPTCs are developed mainly for the applications at around 10 K, while the four-stage ones are to directly achieve the liquid helium temperature. The three-stage and four-stage SPTCs can simultaneously acquire cooling powers at three and four stages, respectively, and both of them can also be used to precool the J-T coolers for further lower temperatures. The typical development programs are introduced and an overview of the cooler performances is presented.